Characteristics of some soils of the medium-amazon river region - Ramos, Doracy Pessoa; Velloso, Ary Carlos X. (Pesquisa Agropecuaria Brasileira, 2014)
A study has been made of five soils selected for characterization by laboratory and field methods in a toposequence of the Parintins area, located in the medium-Amazon River Region. The A horizon, as contrasted with the rest of the solum, have some accumulation of organic matter. The potential cation exchange capacity at pH 7, is related to the organic matter content; the increase of CTC is about 4 meq per 1% carbon. Exchangeable aluminum, pH and base saturation are related to slope position. Soils in the higher slope positions are higher in exchangeable aluminum. Soils in the lower slope positions have the highest base and pH status. The molecular ratio SiO2/Al2O3 (Ki) pointed to a strong predominance of kaolinite in, the clay fraction, which is confirmed by X-ray patterns. The soils studied were classified according to the systems adopted by the USDA (7th approximation), FAO and DPP (Brazil).